Synthesis, characterization, and photocatalytic degradation of Rhodamine B dye under sunlight irradiation of porous titanosilicate (TS)/bismuth vanadate (BiVO4) nanocomposite hybrid catalyst. (1st March 2017) - Adepu, Ajay Kumar; Katta, Vamsi; Narayanan, Venkatathri
Abstract : Present work focuses on the development of hybrid nanocomposites and its application as photocatalyst in the degradation of organic dyes. Abstract : Novel mesoporous titanosilicate/bismuth vanadate (BVTS) inorganic hetero-structures were successfully synthesized under mild conditions. The synthesized mesoporous BVTS hetero-structures were characterized by various analytical techniques for structural and chemical properties. We confirmed from TEM results that a good heterojunction formed between titanosilicate and bismuth vanadate. More significantly, the BVTS hetero-structures exhibited enhanced photocatalytic activity in the degradation of Rhodamine B dye (RhB) under sunlight irradiation. The optimum photocatalytic activity of BVTS 1 under visible light is almost 3.5 and 6.5-fold higher than pure titanosilicate (TS) and pure bismuth vanadate (BVO), respectively. These composites and their photocatalytic Rhodamine-B dye degradation under sun light irradiation is reported for the first time. The popularity of fabrication of heterojunction structures is an inevitable trend. A RhB solution (100 mL, 10 −5 M) was degraded in 60 min using the BVTS nanocomposites photocatalyst with visible light irradiation. The BVTS nanocomposites responded well and thus remarkably enhanced photocatalytic efficiency.